2012
DOI: 10.1523/jneurosci.2278-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating Anterior Insular Cortex Reduces Risk Taking

Abstract: We often have to make risky decisions between alternatives with outcomes that can be better or worse than the outcomes of safer alternatives. Although previous studies have implicated various brain regions in risky decision making, it remains unknown which regions are crucial for balancing whether to take a risk or play it safe. Here, we focused on the anterior insular cortex (AIC), the causal involvement of which in risky decision making is still unclear, although human imaging studies have reported AIC activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 51 publications
5
45
1
Order By: Relevance
“…Within animal studies involving insular cortex manipulations, studies have demonstrated both a role for the CGIC [14,15,17,41,42] or RAIC [16,[43][44][45][46][47] or both [13,48] in addiction relevant behaviors. To our knowledge, only two studies thus far have compared manipulations of the CGIC vs. RAIC and found differential involvement in addiction-relevant behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Within animal studies involving insular cortex manipulations, studies have demonstrated both a role for the CGIC [14,15,17,41,42] or RAIC [16,[43][44][45][46][47] or both [13,48] in addiction relevant behaviors. To our knowledge, only two studies thus far have compared manipulations of the CGIC vs. RAIC and found differential involvement in addiction-relevant behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Activity in the insula is associated with tracking risk (Ishii et al, 2012; Naqvi et al, 2014; Paulus et al, 2003; Kuhnen and Knutson, 2005), and patients with insula lesions make choices that reflect insensitivity to the odds of winning on gambling tasks (Clark et al, 2008). In addition, projections from the midbrain to the striatum signal the presence of motivationally salient events, and anticipatory dopaminergic responses modulate risk preferences (St Onge and Floresco, 2009; Sugam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence implicated the OFC in risk-taking; however, its exact role is still a matter of debate. For instance, transient or permanent OFC inactivation increased, decreased, or left unaffected risktaking and these mixed effects might be accounted for in part by the type of task, time point of inactivation during task acquisition, or targeted OFC subregion (Floresco, St Onge, Ghods-Sharifi, & Winstanley, 2008;Ishii, Ohara, Tobler, Tsutsui, & Iijima, 2012;Jentsch, Woods, Groman, & Seu, 2010;Mobini et al, 2002;Pais-Vieira, Lima, & Galhardo, 2007;Zeeb & Winstanley, 2011). Of note, a recent study using a probabilistic discounting task similar to the one used here showed that OFC lesions promoted risk aversion (Abela & Chudasama, 2013).…”
Section: Ofc Dopamine and Probabilistic Choicementioning
confidence: 69%